Compound odontoma associated with a retained primary upper canine. Case report - Corral Peñafiel, David Francisco (2021)
Compound odontoma is a rare pathology and represents 1.3% of all odontogenic tumors. Its etiology is multifactorial and is attributed mainly to some theories. Also to trauma and genetic factors, etc. Treatment is the enucleation of the entity. The present case is of a 7-year-old male patient who attended the Teaching Dental Center of the Universidad Peruana Cayetano Heredia, Lima - Peru, presenting the absence of tooth 63 and a tumor in the anterosuperior area on the left side. Imaging examinations such as periapical and panoramic radiographs and Cone Beam Computed Tomography (CBCT) were performed; subsequently, the odontogenic tumor was enucleated and tooth 63 was extracted; the presumptive diagnosis was confirmed by the pathological anatomical examination as a compound odontoma. Knowledge of the normal characteristics of the oral cavity and the chronology of tooth eruption can lead to an early diagnosis of a pathology such as odontoma. Allowing to treat the patient in a timely manner, thus avoiding possible complications.